Nerve regeneration by human corneal stromal keratocytes and stromal fibroblasts - Yam, Gary Hin-Fai (2017)
Laser refractive surgeries reshape corneal stroma to correct refractive errors, but unavoidably affect corneal nerves. Slow nerve regeneration and atypical neurite morphology cause desensitization and neuro-epitheliopathy. Following injury, surviving corneal stromal keratocytes (CSKs) are activated to stromal fibroblasts (SFs). How these two different cell types influence nerve regeneration is elusive. Our study evaluated the neuro-regulatory effects of human SFs versus CSKs derived from the same corneal stroma using an in vitro chick dorsal root ganglion model. The neurite growth was assessed by a validated concentric circle intersection count method. Serum-free conditioned media (CM) from SFs promoted neurite growth dose-dependently, compared to that from CSKs. We detected neurotrophic and pro-inflammatory factors (interleukin-8, interleukin-15, monocyte chemoattractant protein-1, eotaxin, RANTES) in SFCM by Bio-Plex Human Cytokine assay. More than 130 proteins in SFCM and 49 in CSKCM were identified by nanoLC-MS/MS. Proteins uniquely present in SFCM had reported neuro-regulatory activities and were predicted to regulate neurogenesis, focal adhesion and wound healing. Conclusively, this was the first study showing a physiological relationship between nerve growth and the metabolically active SFs versus quiescent CSKs from the same cornea source. The dose-dependent effect on neurite growth indicated that nerve regeneration could be influenced by SF density.